Methods of Internalizing Character Values in Early Childhood - Hakiki Putri; Nabila Sayuti; Bismi Oktamadani Rasuliana; Haris Riyadi; Rani Oktaviani (Prodi PG-PAUD, FKIP, Universitas Trilogi, 2026)
This study aims to analyze the strategies and methods for internalizing character values in early childhood through theoretical review and literature analysis. Early childhood is a critical period for character formation, as children aged 0–6 years are highly sensitive to environmental stimuli and social modeling. Despite growing recognition of character education’s importance, many early childhood education (ECE) institutions lack systematic, evidence-based guidance on which pedagogical methods are most effective for instilling specific values. Adopting a descriptive qualitative approach with library research methods, this study examines concepts, patterns, and empirical findings from 40 scholarly sources, including peer-reviewed articles, books, and policy documents published between 2013 and 2024. The analysis reveals that character internalization in early childhood must be implemented through concrete experiences, consistent habituation, social interaction, and authentic examples from significant adults. Three primary methods were identified as effective and complementary: modeling (keteladanan), storytelling or narrative (kisah), and simulation through role-play (simulasi). Modeling provides real-life behavioral examples; storytelling enriches moral understanding through relatable characters and conflicts; simulation enables children to practice values in authentic, peer-based contexts. Core character values emphasized include discipline, responsibility, honesty, empathy, religiosity, and multicultural awareness. The study also identifies key challenges: limited teacher creativity in designing engaging activities, inconsistent parenting styles between home and school, and the absence of long-term evaluation instruments. These findings underscore the necessity of tripartite collaboration among teachers, parents, and the broader community to ensure sustainable character development. This research contributes a practical, integrated framework for ECE practitioners and highlights gaps for future empirical studies, including comparative effectiveness research and longitudinal designs.